Angsana sap vs. povidone-iodine for wound healing in tropical and military settings - Tessalonika Shinta Ratriani; Astheria Eryani; Surachman AJ Didy; Dian Andriani Ratna Dewi (The ASEAN Journal of Military and Preventive Medicine, 2026)
Background: Wound infection remains a significant cause of morbidity in trauma patients, especially in battlefield and tropical settings where access to standard antiseptics is limited. Povidone-iodine 10% is commonly used due to its broad-spectrum antimicrobial activity; however, concerns about cytotoxicity and logistical constraints necessitate alternative antiseptic options. Methods: A narrative review was conducted using literature from PubMed, Scopus, and Google Scholar databases. Relevant studies were identified using combinations of MeSH terms and free-text keywords related to Pterocarpus indicus, natural antiseptics, povidone-iodine, wound infection, and trauma care. Findings were synthesized through thematic analysis. Discussion: Angsana (Pterocarpus indicus) sap contains bioactive compounds such as flavonoids, tannins, and terpenoids with antimicrobial and anti-inflammatory properties. These compounds may contribute to bacterial inhibition and enhanced tissue healing. Compared with povidone-iodine, which offers a broader antimicrobial spectrum, angsana sap may provide supportive effects on wound repair with potentially lower cytotoxicity. Evidence suggests it could serve as an alternative or adjunct in resource-limited environments, particularly in tropical and military contexts. Conclusion: Angsana sap demonstrates promising potential as a natural antiseptic for wound management. However, it cannot yet replace povidone-iodine due to limited clinical evidence. Further well-designed studies are needed to confirm its safety, efficacy, and applicability in clinical practice. Keywords: Pterocarpus indicus, angsana sap, povidone-iodine, wound infection, wound healing.